Change Process in Coaching: Interplay of Nonverbal Synchrony, Working Alliance, Self-Regulation, and Goal Attainment - Erdös, Tünde; Ramseyer, Fabian T. (Frontiers in Psychology, 2021)
Background: Psychological literature emphasizes that self-regulation is important as goal intentions, goal setting or implementation intention do not automatically result in effective results in coaching. The question which coaching strategies to apply toward strengthening clients’ self-regulatory capacities as prerequisites of effective change outcomes remains a black box in coaching. Method: This quantitative study explored clients’ self-regulatory mechanisms by addressing how movement synchrony influences clients’ cognitive and emotional self-regulation across sessions. 184 coach-client pairs and their evolving change process were observed over 8 months. Video-recorded sessions were assessed with Motion Energy Analysis (MEA) to automatically capture coach and client nonverbal behavior and quantify movement synchrony at the level of the dyad. Results: Synchrony was differentially associated with clients’ post-session questionnaires on result-oriented problem and self-reflection, affect balance, and working alliance. Network analyses suggested that the association between synchrony and other process variables did not correspond to the previously found positive association between synchrony and positive aspects of alliance or outcome. Instead, this association depended on the level of perceived outcome. Discussion: Coaching success may be predicted by process variables assessed after each session: Goal reflection, alliance, and mood all predict successful coaching. The assessment of nonverbal synchrony suggests a state-dependent effect of embodied processes on coaching outcome that warrants further inspection.